Effects of Temporal Crop Diversification of a Cereal-Based Cropping System on Generalist Predators and Their Biocontrol Potential - Puliga, Giovanni Antonio; Thiele, Jan; Ahnemann, Hauke; Dauber, Jens (Frontiers in Agronomy, 2021)
In agroecosystems, crop diversification plays a fundamental role in maintaining and regen-erating biodiversity and ecosystem services, such as natural pest control. Temporal diversi-fication of cropping systems can affect the presence and activity of natural enemies by providing alternative hosts and prey, food and refuges for overwintering. However, we still lack studies on the effects of temporal diversification on generalist predators and their bio-control potential conducted at field scale in commercial agricultural settings. Here, we measured proxies of ecosystem functions related with biological pest control in 29 commer-cial agricultural fields characterized by cereal-based cropping system in Lower-Saxony, northern Germany. The fields differed in the number of crops and cover crops cultivated during the previous twelve years. Using the Rapid Ecosystem Function Assessment ap-proach, we measured invertebrate predation, seed predation and activity density of generalist predators. We aimed at testing whether the differences in the crop rotations from the previ-ous years would affect activity of predators and their predation rates in the current growing season. We found that the length of the crop rotation had neutral effects on the proxies measured. Furthermore, predation rates were generally lower if the rotation comprised a higher number of cover crops compared to rotation with less cover crops. The activity densi-ty of respective taxa of predatory arthropods responded differently to the number of cover crops in the crop rotation. Our results suggest that temporal crop diversity may not benefit the activity and efficiency of generalist predators when diversification strategies involve crops of very similar functional traits. Adding different resources and traits to the agroeco-systems through a wider range of cultivated crops and the integration of semi-natural habi-tats are aspects that need to be considered when developing